White lupine (Lupinus albus L.) flours for healthy wheat breads: rheological properties of dough and the bread quality - Guardianelli, Luciano Martín (2023)
Protein-based foods based on sweet lupine are gaining the attention of industry and consumers on account of their being one of the legumes with the highest content of proteins (28–48%). Our objective was to study the thermal properties of two lupine flours (Misak and Rumbo) and the influence of different amounts of lupine flour (0, 10, 20 and 30%) incorporations on the hydration and rheological properties of dough and bread quality. The thermograms of both lupine flours showed three peaks at 77–78 ◦C, 88–89 ◦C and 104–105 ◦C, corresponding to 2S, 7S and 11S globulins, respectively. For Misak flour, higher energy was needed to denature proteins in contrast to Rumbo flour, which may be due to its higher protein amount (50.7% vs. 34.2%). The water absorption of dough with 10% lupine flour was lower than the control, while higher values were obtained for dough with 20% and 30% lupine flour. In contrast, the hardness and adhesiveness of the dough were higher with 10 and 20% lupine flour, but for 30%, these values were lower than the control. However, no differences were observed for G0 , G00 and tan parameters between dough. In breads, the protein content increased ~46% with the maximum level of lupine flour, from 7.27% in wheat bread to 13.55% in bread with 30% Rumbo flour. Analyzing texture parameters, the chewiness and firmness increased with incorporations of lupine flour with respect to the control sample while the elasticity decreased, and no differences were observed for specific volume. It can be concluded that breads of good technological quality and high protein content could be obtained by the inclusion of lupine flours in wheat flour. Therefore, our study highlights the great technological aptitude and the high nutritional value of lupine flours as ingredients for the breadmaking food industry.